Mathematical modeling applied to comminution - Osorio Maza, Mercedes Aida (2014)
Mathematical modeling applied to equipment’s utilized in ore comminution process (crusbing, milling) is so important tool for simulation and optimisation of continuos metallurgical processes (at indudtrial rate), is equivalent, to predict the granulometric yield of a processed ore, by only knowing of feed rate (simulated), obvionsly the model will store intrinsic ly and inherently the plysical properties of ore (hardness, fracture) and equipment operation conditions (CSS opening). The better performance obtained in this manner of the equipment will certaimly contribute for a good consequence in future ore processing worhs.